PENGARUH PROTEAN CAREER ATTITUDE TERHADAP PROACTIVE WORK BEHAVIOR DENGAN MEDIASI PASSION FOR WORK PADA GENERASI MILENIALS DI DKI JAKARTA - Susi Lidya Magdalena (Prosiding Working Papers Series In Management, 2018)
The purpose of this thesis is to examine the effect of protean career attitude (PCA) and proactive work behaviors (PWB) by making passion for work (PFW) as a mediator of the two previous variables. Population is  millennials who are working in DKI Jakarta Sample with purposive sampling and we found 77 respondents In measuring the hypothesis of direct influence from PCA and PWB, simple regression is used while in measuring the influence of mediation on PCA and PWB multiple regression analysis is used. The findings obtained from this study are the protean career attitude (PCA) influencing proactive work behavior (PWB) directly and passion for work (PWF) influencing proactive work behavior (PWB). But the protean career attitude (PCA) has no effect on passion for work (PFW). Companies that have employees who are millennials must be able to establish a human resource management program that can improve the proactive work behavior of their employees. Keywords: Proactive work behavior, Passion for work, Proactive work behavior